Clinical Value of 18F-FDG PET/CT Scan and Cytokine Profiles in Secondary Hemophagocytic Lymphohistiocytosis in Idiopathic Inflammatory Myopathy Patients: A Pilot Study - Liang, Junyu; Cao, Heng; Wu, Bowen; Liu, Yinuo; He, Ye; Xu, Bei; Sun, Yiduo; Ye, Bingjue; Lin, Jin (Frontiers in Immunology, 2021)
Background Secondary hemophagocytic lymphohistiocytosis (sHLH) is a rare but fatal complication in idiopathic inflammatory myopathy (IIM) patients. The clinical value of radiological manifestations and serum cytokines remain unknown in this systemic crisis. This study aims to investigate the clinical value of PET/CT scan and cytokine profiles in predicting and understanding sHLH in IIM patients. Methods Adult IIM patients who were admitted to the four divisions of the First Affiliated Hospital, Zhejiang University School of Medicine (FAHZJU) from January 1, 2017 to December 31, 2020 were reviewed. PET/CT scan, cytokine profiles, and other factors of patients who met the inclusion and exclusion criteria were collected and analyzed. Results Sixty-nine out of 352 IIM patients were finally enrolled into the study. Ten patients developed sHLH and 70.0% of them died within 6 months. After false discovery rate (FDR) correction and multivariate logistic regression analysis, increased serum interferon (IFN)-γ level (p = 0.017), higher spleen mean standard uptake value (SUVmean, p = 0.035), and positivity of anti-MDA5 antibody (p = 0.049) were found to be significantly correlated with development of sHLH in IIM patients. The combination of serum IFN-γ, spleen SUVmean, and anti-MDA5 antibody found a balanced and satisfying predictor with a cutoff value of 0.047 and AUC of 0.946. A moderate correlation was identified between ferritin and spleen SUVmean (p = 0.001, r = 0.380) as well as serum IFN-γ(p = 0.001, r = 0.398). Before FDR correction, higher bilateral lung SUVmean (p = 0.034) and higher colon/rectum SUVmean (p = 0.013) were also observed in IIM patients who developed sHLH. By narrowing down to IIM patients with sHLH, anti-MDA5-antibody-positive DM patients tended to suffer from unfavorable outcome (p = 0.004) in Kaplan–Meier survival analysis. Conclusion Increased serum level of IFN-γ, elevated splenic FDG uptake, and positivity of anti-MDA5 antibody were significantly correlated with development of sHLH in IIM patients. Lung and lower digestive tract might also be affected due to systemic immune activation in IIM patients with sHLH. In addition, splenic FDG uptake, in combination with serum IFN-γand anti-MDA5 antibody, was found valuable in predicting development of sHLH in IIM patients. Among IIM patients with sHLH, anti-MDA5-antibody-positive DM patients showed higher tendency for unfavorable outcome.